2020
DOI: 10.52131/joe.2020.0101.0011
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tax Revenue, Government Expenditures, Fiscal Decentralization, Carbon Emission and Exports on Economic Growth of Developing Countries

Abstract: Nowadays, the achievement of high economic growth is a significant task for every country around the globe and also gain the attention of the researchers. Therefore, the present study purpose is to examine the role of tax revenue, government expenditures, fiscal decentralization, carbon emission and exports on the economic growth of developing countries. The data has been gathered from the World Development Indicator (WDI) for the year 2008-2019 from fifteen emerging developing countries around the globe. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…According to the results, adopting stimulative fiscal spending lowered pollution from both origins of the contaminant, but austerity tax reductions boosted the usage of Carbon footprints. Maneerat and Fazal [13] employed the extended technique of moments to examine the relationship between tax income, state spending, financial intermediation, carbon emissions, exporting, and the infrastructure prosperity of emerging nations from 2008 to 2019. The findings found that all indicators, including tax income, government spending, liberalization, carbon emissions, and exporting, had a good association with developing-country industrial prosperity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the results, adopting stimulative fiscal spending lowered pollution from both origins of the contaminant, but austerity tax reductions boosted the usage of Carbon footprints. Maneerat and Fazal [13] employed the extended technique of moments to examine the relationship between tax income, state spending, financial intermediation, carbon emissions, exporting, and the infrastructure prosperity of emerging nations from 2008 to 2019. The findings found that all indicators, including tax income, government spending, liberalization, carbon emissions, and exporting, had a good association with developing-country industrial prosperity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The government spends for public goods and services which comprise cleaning the environment to prevent air and water pollution. Taxes are important stream of revenue for macroeconomic management and designing; even financial strategies are based on predicted tax collections, and tax plans are a vital feature of every state's financial strategy [13]. Every country needs to generate tax income to fund major government investments in order to preserve its international competitiveness in the global market [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Government spending aims to increase production capacity in projects that refer to economic growth, equal distribution of income, increase in welfare, and programs that directly touch underdeveloped areas. An increase in expenditure, in general, can lead to a more considerable increase in economic output because spending by one individual, household, business, or the government is income for another (Maneerat, 2020). Therefore, there is an urgency for the government to control and manage the economy through the central bank.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Adequate money supply is key to ensure the viability of economic activities but must be controlled to prevent inflation. Taxation is a crucial revenue source for broader economic managing; even budgetary strategies are built on anticipated tax receipts, and tax plans are an essential component of every state's investment plan (Maneerat, Fazal, 2020). To maintain its international competitiveness in the global market, every country must generate tax revenue to fund major government investments (Maneerat, Fazal, 2020).…”
Section: Introductionmentioning
confidence: 99%